Research of extracting, separating and purification technology of laver polysaccharide - LIU Qing-mei; YANG Xing-min; DENG Hong-xia; YANG Liu-ming; WU Ying-long (浙江大学学报. 农业与生命科学版, 2005)
Compared the hot water extracting method with the microwave extracting method in laver polysaccharide, the effect on the quality of laver polysaccharide of removing protein, concentrating, precipitating and drying were investigated and the ingredients of laver polysaccharide were also identified. The result showed that microwave extracting method was more effective than that of hot water extraction, and the extraction efficiency of the microwave freeze melt extracting method was the best, and the max value was up to 7.45%. The proteins in the rough laver polysaccharide were removed with the Sevag method after hydrolyzed by protease. It was proved that this method was the best. In addition, the result suggested that the quality of the laver polysaccharide treated by the vacuum-freeze drying was the best, and the laver polysaccharide consists of galactose, mannose, glucose and xylose.